VALIDATION OF EXTENDED ELASTIC IMPEDANCE BASED ON MINIMUM ENERGY ANGLE. A CASE STUDY APPLICATION FOR OPTIMIZED PETROLEUM RESERVOIR CHARACTERIZATION - Habib, Mukhtar; Abba, Bashir Aliyu; Alhassan, Aminu Uba; Umar, Jibia Firdausi (FUDMA Journal of Sciences, 2022)
This work intends to showcase a validation of the applicability of Extended Elastic Impedance (EEI) inversion method in reservoir characterization and modeling. In order to achieve that, deterministic seismic inversion and extended elastic impedance (EEI) analysis were applied to obtain quantitative estimates of reservoir properties over the Pu field of the West African Congo basin. Optimum EEI angles corresponding to the reservoir properties were then analyzed using well logs data, together with a lithology indicator.  Pre-stack seismic data were simultaneously inverted into density, acoustic and gradient impedances cubes, through model based inversion algorithm. The last two broadband inverted volumes were then projected to corresponding Chi angles proportionate to petrophysical indicators, thus resulting to two broadband EEI volumes. At well locations, the EEI versus petrophysical parameters linear trends were then applied to convert EEI volumes into  porosity and shale volumes based on specified lithology. In order to generate reservoir facies distribution, minimum angle was applied based on background EEI, thus allowing for mapping of reservoir facies. In order to validate the EEI approach, a Geo-statistical model was further developed for the same field. Hence, from  porosity, shale content and background EEI cubes, a comparison was made between the properties generated from the EEI and that generated based on geo-statistical method, which shows that EEI is a robust way of reservoir characterization that  pinpointing favorable reservoir potentials which shall guide future drilling locations.
Keywords: Extended Elastic Impedance, Reservoir Geo-statistical model, Minimum Energy Angle and Facies; Extended Elastic Impedance; Reservoir Geo-statistical model; Minimum Energy Angle; Facies